Students’ Error In Using Simple Present Tense Mastery - Siswoyo, Siswoyo (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This paper is to know the students’ error in using simple present tense. The data were the second semester students’ structure 1 final written examination answer. After analyzing the second semester students’ structure 1 answer, it was found that the students made error in using simple present tense. These errors are categorized into omission, addition, misordering and misformation. The most errors made by the students are misformation error.